Primer registro para San Luis Potosí y nuevos registros para Jalisco de mycocepurus smithii (forel, 1893) (hymenoptera: formicidae) - Vasquez-Bolaños, Miguel (Instituto de Ecología, A.C., 2007)
First record of the fungus-wronging ant Mycocepurus smithii for the state of San Luis Potosí and new record locality for Jalisco state, amplying north limit for this species.